Interaction of the Human Contact System with Pathogens—An Update - Oehmcke-Hecht, Sonja; Köhler, Juliane (Frontiers in Immunology, 2018)
The name human contact system is related to its mode of action, as "contact" with artificial negatively charged surfaces triggers its activation. Today it is generally believed that the contact system is an inflammatory response mechanism - not only against artificial material - but also against misfolded proteins and foreign organisms. Upon activation, the contact system is involved in at least two distinct (patho)physiologic processes: i. the trigger of the intrinsic coagulation via factor XI ii. the cleavage of high molecular weight kininogen with release of bradykinin and antimicrobial peptides. Bradykinin is involved in the regulation of inflammatory processes, vascular permeability, and blood pressure. Due to the release of antimicrobial peptides the contact system is regarded as a branch of the innate immune defense against microorganisms. There is an increasing list of pathogens who interact with contact factors, in addition to bacteria also fungi and viruses bind and activate the system. In spite of that, pathogens have developed their own mechanisms to activate the contact system, resulting in manipulation of this host immune response. In this up-to-date review, we summarize present research on the interaction of pathogens with the human contact system, focusing particularly on bacterial and viral mechanisms that trigger inflammation via contact system activation.